A imagem-superfície em Takashi Miike - Madeira, Eduardo Costa (2017)
Takashi Miike's movies, in nonsense and ultra violent dimensions that circumspect them, seems to say not so much about representation, but they arrest the spectatorship in the experience of image in the means of a surface, with the same brutality that we